ONLINE WRITELOGUE EFFECTIVENESS IN THE STUDENTS’ MASTERY OF THE REDUCED RELATIVE CLAUSES - Hendra Tedjasuksmana; Susana Teopilus (Magister Scientiae, 2020)
In this pandemic Covid-19 situation, all teaching learning activities are done online from the elementary school up to the universities. What the writers would do is actually implementing a blended learning, but Covid19 makes it impossible so that it is done fully online. Thus, this study would find out that the full-online platform writelogue with its module can improve the students’ ability in using the reduced relative clauses. This module in which the students learn the NP pattern ‘HN (Head Noun) + reduced relative clauses’ is one of a number of NP patterns in the writers’ multi-year research. Using the accessibility of the Learning Manangement System, the writelogue, the students did the pre-test, the exercises and the post-test. Besides, they filled out the questionnaire concerning the usability of the writelogue in terms of language, exercises, tutorial video, and technical operation. The results show that the online writelogue course enhances the pre-test scores of the students in their post-test result, and the students find the benefits of the writelogue course to their learning the reduced relative clause on line.